The impact of imprisonment on health: what do women prisoners say?. Issue 9 (23rd April 2009) - Douglas, N; Plugge, E; Fitzpatrick, R
Abstract : Background: Women prisoners tend to suffer poor health on a range of indicators. This study sought to explore women prisoners' perceptions of the impact of imprisonment on their health. Methods: This qualitative study involved adult women prisoners in two closed local prisons. Focus groups and individual interviews were conducted. Results: Women prisoners reported that imprisonment impacted negatively upon their health. The initial shock of imprisonment, separation from families and enforced living with other women suffering drug withdrawal and serious mental health problems affected their own mental health. Over the longer term, women complained of detention in unhygienic facilities by regimes that operated to disempower them, including in the management of their own health. Women described responses to imprisonment that were also health negating such as increased smoking, eating poorly and seeking psychotropic medication. However, imprisonment could also offer a respite from lives characterised by poverty, social exclusion, substance misuse and violence, with perceived improvements in health. Conclusion: The impact of imprisonment on women's health was mixed but was largely perceived to be negative. Despite policy initiatives to introduce health promotion in prisons, there is little evidence of the extent to which this has been effective. The current policy climate in the UK makes it especially timely to examine the reported experience of women prisoners themselves about the impact of imprisonment on their health and to re-evaluate health promotion in women's prisons.